Beginning T-SQL 2008 - Kellenberger, Kathi (New York, NY. : Apress ; Distributed by Springer-Verlag, 2009)
This book will teach you about databases, normalization, and SQL Server Management Studio. You will learn how data is stored in a database and how to use at least one of the available tools to get to that data. Each subsequent chapter teaches an aspect of T-SQL, building on the skills learned in previous chapters. Exercises are included in each chapter because the only way to learn T-SQL is to write some code. This book will do more than just give the syntax and examples. It will teach you techniques to help you avoid common errors and how to create robust and well-performing code, you will learn the best practices for writing T-SQL, it will help readers avoid common errors, and show you how to write scalable code that yields good performance.
Getting started -- Writing simple SELECT queries -- Using functions and expressions -- Querying multiple tables -- Grouping and summarizing data -- Manipulating data -- Understanding T-SQL programming logic -- Moving logic to the database -- Working with new data types -- Writing advanced queries -- Where to go next? -- Solutions to the exercises.
"Books for professionals by professionals"--Cover
"Quickly move beyond beginner status with this step-by-step approach to learning T-SQL" --Cover.
Includes index.
Keywords: SQL server; SQL server (Computer software); SQL (Computer program language); Database management; Client/server computing; SQL (Computer language)